2009
DOI: 10.1097/tp.0b013e3181ac68a9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deceased Donor Diabetes Mellitus on Kidney Transplant Outcomes: A Propensity Score-Matched Study

Abstract: The long-term graft survival of KTR with DM donors is significantly inferior to non-DM donors, but the absolute difference is small. DM donors do not adversely impact patient survival. This suggests that DM donors may be effectively used to expand the donor pool, but evidence-based guidelines on the appropriate selection of these donors are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…Donor diabetes has been shown to be associated with inferior graft survival in kidney transplant recipients (27,28); however, the association of donor diabe-tes with liver transplant outcome is unclear. Donor diabetes has been shown to be associated with inferior graft survival in kidney transplant recipients (27,28); however, the association of donor diabe-tes with liver transplant outcome is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Donor diabetes has been shown to be associated with inferior graft survival in kidney transplant recipients (27,28); however, the association of donor diabe-tes with liver transplant outcome is unclear. Donor diabetes has been shown to be associated with inferior graft survival in kidney transplant recipients (27,28); however, the association of donor diabe-tes with liver transplant outcome is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It allows simultaneous adjustments for multiple confounders (42)(43)(44). Traditionally, matching in observational cohort studies has been done manually.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmad et al noted similar patient survival, but slightly inferior graft survival in recipients of deceased diabetic donor kidneys when compared to recipients of deceased non‐diabetic donor kidneys. Due to the small absolute difference, the authors concluded that diabetic donors could be used to expand the donor pool . In 2012, Mohan et al demonstrated that donor diabetes did not have a significant effect on graft and patient survival and even suggested that diabetic donor kidneys may be superior to using extended criteria donor kidney .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small absolute difference, the authors concluded that diabetic donors could be used to expand the donor pool. 3 In 2012, Mohan et al demonstrated that donor diabetes did not have a significant effect on graft and patient survival and even suggested that diabetic donor kidneys may be superior to using extended criteria donor kidney. 4 Recently, Cohen et al reported discordant recipient pair analysis of diabetic donor kidneys, using United Network of Organ Sharing data, and found that although a risk was associated with diabetic donor kidneys, it was dependent on recipient diabetes status.…”
Section: Introductionmentioning
confidence: 99%